ASPEK HUKUM DALAM TRADISI BEREMBO’ PADA KELUARGA MEMPELAI PRIA KETURUNAN BUGIS MELAYU DI PONTIANAK PADA MALAM SEBELUM PERNIKAHAN - Hafizd Asyqar Dhiya 'Ulhaq; Marluwi Marluwi; Ishar Pulungan (Al-Usroh, 2025)
This article examines the berembo’ tradition within the Bugis-Malay community of Pontianak as a complex socio-religious phenomenon. Practiced on the night before the marriage contract, this ritual is often perceived as a customary necessity, even believed to affect the perfection (afdhal) of the wedding. This raises a fundamental question regarding its legal position within the framework of Islamic law, given that it is not part of the pillars or conditions of marriage. This research has three main objectives: (1) to describe the procession and socio-cultural meanings of the berembo’ tradition; (2) to analyze the community's perception of the consequences if this tradition is neglected; and (3) to examine the tradition's legitimacy through the lens of the theory of ‘urf (recognized custom) in Islamic jurisprudence. This study employs a qualitative method with descriptive-empirical and normative approaches. Data were collected through participatory observation, in-depth interviews with five practitioners of the tradition and one customary leader, and documentary study. Data analysis followed the interactive model of Miles and Huberman through the stages of reduction, display, and verification. The findings reveal that berembo’ functions as a mechanism for the groom's mental, spiritual, and social preparation, as well as a space for consolidating family and religious values through advice and prayers from elders. From an Islamic law perspective, this tradition is categorized as ‘urf shahih (valid custom) as it contains no elements of polytheism (shirk), heresy (bid’ah), or contradiction with sharia principles. Thus, this research argues that berembo’ represents a form of living law that harmonizes local cultural values and religious norms, justifying its preservation as long as it is not claimed as a religious obligation. This article contributes to the discourse on juridical harmonization in pluralistic societies by offering an integrative analytical framework between legal anthropology and fiqh.